2003
DOI: 10.1093/ptr/kpg027
|View full text |Cite
|
Sign up to set email alerts
|

Respective Contributions of Therapist and Client Adult Attachment Orientations to the Development of the Early Working Alliance: A Preliminary Growth Modeling Study

Abstract: The authors investigated the temporal relationship between client and therapist attachment orientations and early working alliance. Attachment was measured by self-report after the 1st session of therapy. The working alliance ratings were completed after the 1st, 4th, and 7th therapy sessions. Hierarchical linear modeling results indicated that anxiously attached therapists had a significant positive effect on the client working alliances after the 1st session but significant negative effects over time. No oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
6
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(138 citation statements)
references
References 39 publications
10
115
6
3
Order By: Relevance
“…Although little empirical support is available regarding IPNB specifically, aspects of IPNB including attachment theory, mindfulness, and psychoeducation have growing bodies of empirical support. Researchers have found evidence to substantiate links between counselors' attachment styles and aspects of the therapeutic process Saucer et al, 2003;Schauenburg et al, 2010;Tyrrell et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Although little empirical support is available regarding IPNB specifically, aspects of IPNB including attachment theory, mindfulness, and psychoeducation have growing bodies of empirical support. Researchers have found evidence to substantiate links between counselors' attachment styles and aspects of the therapeutic process Saucer et al, 2003;Schauenburg et al, 2010;Tyrrell et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Although, interestingly, it has also been found that attachment style, particularly client avoidance or anxiety has no effect upon therapeutic alliance (Sauer, Lopez & Gormley, 2003;Reis & Grenyer, 2004). Moreover, to date, no published attachment-based research has focused solely on the clinical population of PTSD (Smith & Golding, 2010).…”
Section: Ptsd/trauma Have Been Experienced Over the Past 35 Years In mentioning
confidence: 99%
“…research on psychotherapy has suggested that the ability to build an effective alliance with patients may be related to the therapist's attachment style [17]. There is a significant relation between the 'secure' and 'insecure' attachment style in clinical psychologists and their clinical practices [18].…”
Section: Model Of Self (Dependence)mentioning
confidence: 99%